2012
DOI: 10.5194/hessd-9-13251-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Groundwater-surface water interactions, vegetation dependencies and implications for water resources management in the semi-arid Hailiutu River catchment, China – A synthesis

Abstract: During the last decades, large scale land use changes took place in the Hailiutu River catchment, a semi-arid area in northwest China. These changes had significant impacts on the water resources in the area. Insights into groundwater and surface water interactions and vegetation-water dependencies help to understand these impacts and formulate sustainable water resources management policies. In this study, groundwater and surface water interactions were identified using the baseflow index at the catchment sca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Chen et al (2013) found that S. psammophila consumes more water than A. ordosica based on diurnal water table fluctuation. Moreover, Zhou et al (2013) confirmed that S. psammophila consumes more water than Salix matsudana at the Hailiutu river catchment. Therefore, S. psammophila might not be a suitable species for stabilizing sand dunes in water-scarce environments.…”
Section: Discussionsupporting
confidence: 78%
“…Chen et al (2013) found that S. psammophila consumes more water than A. ordosica based on diurnal water table fluctuation. Moreover, Zhou et al (2013) confirmed that S. psammophila consumes more water than Salix matsudana at the Hailiutu river catchment. Therefore, S. psammophila might not be a suitable species for stabilizing sand dunes in water-scarce environments.…”
Section: Discussionsupporting
confidence: 78%
“…For semi-arid areas such as our study area, a delicate balance among vegetating sand dunes, agricultural production, and water resources conservation must be maintained [44]. Over-vegetating sand dunes with high water consumption species (such as poplar trees and salix bushes) would reduce net groundwater recharge and diminish stream flows.…”
Section: Scenario Analysismentioning
confidence: 99%
“…Remote sensing data can be employed for estimating the ET by means of energy balance methods, statistical methods using the difference between surface and air temperature, surface energy balance models, and spatial variability methods at different scales [38]. Remote sensing and the Normalized Difference Vegetation Index (NDVI) have been widely employed for estimating groundwater evapotranspiration [39,40], investigating the relationship between vegetation growth and depth to groundwater table [41][42][43][44], and accessing groundwater recharge fluxes [45]. Many researchers have conducted direct measurements like the sap flow method which uses the stem heat balance technique [46], and scaled these values to the catchment level transpiration [47].…”
Section: Introductionmentioning
confidence: 99%
“…These reforestation projects have prevented further deterioration of arid regions and have rehabilitated the eco-environment. However, recent research has revealed side effects stemming from the improper selection of plants [5], such as the decay of re-vegetation and a decrease in groundwater levels [6]. In arid areas, water resources are extremely scarce and the environment is very fragile.…”
Section: Introductionmentioning
confidence: 99%